2018
DOI: 10.12816/0043981
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation between Infants’ Congenital Heart Defects and Maternal Folic Acid Supplementation

Abstract: Background: Congenital heart defects (CHDs) are significant drivers of mortality and morbidity in children, folic acid supplementation for the pregnant month during or before delivery is said to influence risk reduction of congenital heart defects (CHDs). However, there are controversial claims and the hypothesis is concluded from limited epidemiologic studies. Aim of the Study: Conduct a systematic review and metaanalysis of published studies to reliably evaluate the correlation between Folic acid or multivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…Cousin marriage can cause congenital heart defects (18). Congenital cardiovascular malformations are common in these associations and affect 2.4 to 8.0 in 1000 infants (19). In our study, prenatal cardiac findings were found in 15 fetuses.…”
Section: Discussionsupporting
confidence: 50%
“…Cousin marriage can cause congenital heart defects (18). Congenital cardiovascular malformations are common in these associations and affect 2.4 to 8.0 in 1000 infants (19). In our study, prenatal cardiac findings were found in 15 fetuses.…”
Section: Discussionsupporting
confidence: 50%
“…Regarding use of folic acid which is supposed to play role in prevention of CHD was taken by only 20% of mothers during pregnancy which was found significant with p value <0.01 Metaanalysis by Hassan et al and Feng reports intake of folic acid by mothers significantly decreased risk of CHDs. Another study reports marked decline in various CHDs including ventricular septal defect, tetralogy of Fallot, transposition of great arteries and atrial septal defect in infants born to mothers who had taken high doses of folic acid during the critical period of CHD development [14,15,16].…”
Section: Resultsmentioning
confidence: 99%
“…Cousin marriage may also cause inborn heart disorders. Inborn cardiovascular malformations are widespread, affecting 2.4 to 8.0 per 1000 infants [7]. Imperfect formation of an embryo or abnormal growth may cause formational deformities in fetus referred as birth defects.…”
Section: Introductionmentioning
confidence: 99%